2021
DOI: 10.1038/s41467-021-22676-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer organoids analyzed on microwell arrays predict drug responses of patients within a week

Abstract: While the potential of patient-derived organoids (PDOs) to predict patients’ responses to anti-cancer treatments has been well recognized, the lengthy time and the low efficiency in establishing PDOs hamper the implementation of PDO-based drug sensitivity tests in clinics. We first adapt a mechanical sample processing method to generate lung cancer organoids (LCOs) from surgically resected and biopsy tumor tissues. The LCOs recapitulate the histological and genetic features of the parental tumors and have the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 53 publications
4
153
0
1
Order By: Relevance
“…In a recent publication by Hu et al, a similar minimal medium composition was used for short-term organoid culture. The authors only used early-passage organoids for further analyses, but reported a high success rate of 79% in early lung cancer organoid establishment [ 17 ].…”
Section: Lung Cancer Organoid Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent publication by Hu et al, a similar minimal medium composition was used for short-term organoid culture. The authors only used early-passage organoids for further analyses, but reported a high success rate of 79% in early lung cancer organoid establishment [ 17 ].…”
Section: Lung Cancer Organoid Methodologymentioning
confidence: 99%
“…Based on morphological and immunohistochemical data, Dijkstra et al described different phenotypes of organoids derived from intrapulmonary NSCLC: NSCLC organoids can be both cystic or solid, although most cancer organoids appear to grow as irregularly formed, solid structures [ 16 ]. In general, there appears to be no clear association between the parental tumor histology and the general NSCLC organoid morphology and architecture [ 17 ]. p63 staining is either disorganized (in squamous cell carcinoma) or absent (in adenocarcinoma), but without a clear polarization within the organoid.…”
Section: Characterization Of Primary Non-small Cell Lung Cancer Organoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer organoids show promise for cancer research by recapitulating the tumor characteristics and heterogeneity [ 9 ]. The use of lung cancer organoids (LCOs) enable reliable high-throughput drug screening [ 10 , 11 , 12 ]. However, the success rate of LCO culture, the culture medium composition, and tissue processing differ among studies.…”
Section: Introductionmentioning
confidence: 99%